Successful management of a Clostridioides difficile ribotype 027 outbreak with a lean intervention bundle. Issue 2 (October 2020) - Kuenzli, A.B.; Burri, S.; Casanova, C.; Sommerstein, R.; Buetti, N.; Seth-Smith, H.M.B.; Bodmer, T.; Egli, A.; Marschall, J.
Summary: Background: In a 2015 point-prevalence study, Clostridioides difficile 027, a hypervirulent ribotype, was absent from healthcare institutions in Switzerland. In late 2016, we detected an outbreak of C. difficile infection (CDI) with ribotype 027 occurring across several hospitals in the same hospital network. Methods: The first cases of CDI due to ribotype 027 triggered an outbreak investigation, including whole genome sequencing (WGS) to identify outbreak strains. Findings: Twenty-eight patients with CDI caused by ribotype 027 between December 2016 and December 2017 were identified, out of which 20 were caused by a single clone. Commonalities among these patients were hospitalization in the same room or on the same ward, receiving care from the same healthcare workers, and shared toilet areas. In addition to the epidemiological links suggesting possible transmission pathways between cases, WGS confirmed the clonality of this C. difficile 027 outbreak. The outbreak was contained by isolation precautions, raising awareness among healthcare workers, harmonizing diagnostic algorithms, and switching to a sporicidal agent for environmental disinfection. Of note, neither default gowning and gloving nor hand washing with water and soap were implemented. Conclusion: This C. difficile 027 outbreak was recognized belatedly due to lack of screening for this ribotype in some hospitals, and was contained by a swift response with simple infection prevention measures and adapting the laboratory approach. In order to have a better understanding of C. difficile epidemiology, diagnostic approaches should be standardized, CDI declared notifiable, and longitudinal data on prevalent ribotypes collected in countries where this is not established.